A rare case of complex variant translocation of t(9;22;16)(q34;q11.2;q24) in a newly diagnosed patient with chronic myeloid leukemia. (2022) - Grant, Bradley J.; Tang, Zhenya; Toruner, Gokce A.; Mahdi, Ali; Bigham, Lindsay; Dong, Jianli; Musunuru, Tejo; Mallick, Jayati; Lyapichev, Kirill A.
Highlights: Complex Philadelphia chromosome translocations. Variability of chromosomal translocations may impact treatment. Genomic analysis is integral for molecular characterization of CML. Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm associated with the dysregulated production of myeloid cells. The Philadelphia chromosome (Ph), t(9;22)(q34;q11), is a hallmark of the disease and found in 90–95% of diagnosed CML patients. The balanced, reciprocal translocation places the genes BCR and ABL1, next to each other, resulting in an increase of kinase activity. Additional cases involve complex variants, including translocation events involving an additional chromosome with the creation of the Ph chromosome. A rare three-way Ph chromosome complex variant, t(9;22;16)(q34;q11.2;q24), was identified in a 40-year-old female who presented with visual changes and leukocytosis. Cytogenetic analysis by G-banding revealed the presence of a three-way translocation involving the long arms of chromosomes 9, 22, and 16. Fluorescence in situ hybridization with a dual-color fusion probe confirmed the presence of the BCR::ABL1 fusion.